2019
DOI: 10.3390/cells8070703
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics in the World of Induced Pluripotent Stem Cells

Abstract: Omics approaches have significantly impacted knowledge about molecular signaling pathways driving cell function. Induced pluripotent stem cells (iPSC) have revolutionized the field of biological sciences and proteomics and, in particular, has been instrumental in identifying key elements operating during the maintenance of the pluripotent state and the differentiation process to the diverse cell types that form organisms. This review covers the evolution of conceptual and methodological strategies in proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 140 publications
0
10
0
6
Order By: Relevance
“…Similar outcomes were described in a study showing an analogous result at the proteome level. In contrast, the differences between ESCs and iPSCs could be depicted only when more biological replicated were added, most likely because this variability was introduced by the inclusion of different donors [100].…”
Section: Similarities and Differences Between Ipscs And Escsmentioning
confidence: 99%
“…Similar outcomes were described in a study showing an analogous result at the proteome level. In contrast, the differences between ESCs and iPSCs could be depicted only when more biological replicated were added, most likely because this variability was introduced by the inclusion of different donors [100].…”
Section: Similarities and Differences Between Ipscs And Escsmentioning
confidence: 99%
“…7,9 More importantly, stem and cancer cell lines exhibit relatively higher diversity in protein expression. Two groups, Lindoso et al 19 and Signer et al, 20 showed that cells with stem-like characteristics possessed greater protein diversity and a higher synthesis rate because stem cells lose some gene expression after differentiation into various types of somatic cells. 21,22 Cancer cells are expected to have a higher diversity of protein expression because they acquire some genetic features of stem cells after transformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Cell lines are considered alternative sources for MP identification because they possess the corresponding tissue characteristics but have a relatively even distribution of protein abundance. , More importantly, stem and cancer cell lines exhibit relatively higher diversity in protein expression. Two groups, Lindoso et al and Signer et al, showed that cells with stem-like characteristics possessed greater protein diversity and a higher synthesis rate because stem cells lose some gene expression after differentiation into various types of somatic cells. , Cancer cells are expected to have a higher diversity of protein expression because they acquire some genetic features of stem cells after transformation. For instance, Sato et al developed mouse xenograft models of brain cancer metastasis by intracardiac injection of human breast cancer cell lines and observed that metastasis-related genes were specifically upregulated in both brain tissue and cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…It is an analytical pattern in wide ranges to identify, measure and understand post translational concerning of protein in a tissue or cell or body fluid. 1 Proteomic approaches represented an instrumental in providing information of diseases on molecular basis, clear understanding of pathophysiology, prediction of disorders thereby conferred standardized thrust, aiming at therapeutic solutions. Proteomic tools contribute a new clarity for health risk factors and have been recognized as a novel science instead of collection of tools.…”
Section: Introductionmentioning
confidence: 99%